Near‐seabed sediment dynamics and fluxes on Chatham Rise, the effects of seabed disturbance, and implications for deep‐sea bottom trawling and seabed mining - Scott D. Nodder; Christopher A. Eager; Joe O’Callaghan; Daniel Leduc; Sam Davidson; Stacy Deppeler; Grace Frontin‐Rollet; Peter Gerring; Sarah Searson; William Quinn; Steve George; Ron Ovenden; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
Anthropogenic impacts are increasingly affecting deep‐sea environments, including seafloor sediment disturbances by bottom trawling and seafloor mining. Fieldwork in the ‘Resilience Of Benthic Ecosystems to Sedimentation’ (ROBES) project were conducted in 2018–2020 on the 400 m‐deep Chatham Rise crest, eastern Aotearoa New Zealand. Water column turbidity data, sediment traps on near‐seabed moorings and benthic landers and surficial sediments from multi‐corers provided baseline and post‐impact information following an artificially induced seafloor disturbance event in June 2019 using a modified harrow plough in and around an elongated bathymetric depression, designated as the ‘Butterknife’. During the disturbance, total mass and particulate organic carbon (POC) near‐bed fluxes were elevated above long‐term fluxes (2018–20). Long‐term 2018–19 fluxes were generally less than in 2019–20, driven by interannual oceanographic variations. These results, coupled with 50–100 m‐thick benthic boundary layers, suggest that lateral advection is a dominant process in the resuspension and redistribution of seafloor sediments on the rise. Further research is required to better understand the longer term dynamics of particle transport and deposition in response to human activities, such as bottom trawling or proposed phosphorite seafloor mining, especially in bathyal environments, such as the Chatham Rise.

Effects of an experimental in situ seabed disturbance on deep‐sea benthic ecosystem function and macro‐infaunal community structure on the Chatham Rise, Southwest Pacific - Rachel Hale; Daniel Leduc; Campbell Murray; Ashley A. Rowden; Scott D. Nodder; Chris Eager; Rob Stewart; Christopher W. Hickey; Conrad Pilditch; Malcolm R. Clark (New Zealand Journal of Marine and Freshwater Research, 2025)
Expansion of extractive industries to deep‐sea environments will lead to increased stresses on seafloor ecosystems. We examined changes in environmental parameters following direct and indirect experimental benthic disturbance using a modified plough on the Chatham Rise (∼450 m water depth), Aotearoa/New Zealand. Measurements included sediment community oxygen consumption (SCOC), nutrient fluxes, macro‐infauna community composition, and sediment organic carbon (C) and nitrogen (N) content. We observed an increase in SCOC immediately after the disturbance, alongside a decrease in macro‐infauna abundance, biomass, species richness, and diversity, and an increase in sediment C:N. One‐year after the disturbance, SCOC and sediment C:N ratios were similar to that of pre‐disturbance levels, while macro‐infauna abundance and biomass were greater. We observed a shift in the community structure at directly disturbed sites one‐year post‐disturbance with decreased biomass of Polychaeta and increased biomass of Ophiuroidea. No changes were observed in sediment nutrient fluxes. Our study indicates the Chatham Rise benthic ecosystem was initially negatively affected by the disturbance, but the recovery of many parameters after one‐year shows the potential resilience of the ecosystem. Compared to many proposed deep‐sea resource extraction sites the Chatham Rise experiences a relatively high‐level of anthropogenic and natural disturbance which may explain the relatively rapid recovery. Seafloor resilience to human disturbances and recovery from impacts will depend on local environmental conditions that need to be evaluated by environmental impact assessments. This knowledge will be key to predicting and mitigating disturbance impacts. While the Chatham Rise is relatively well studied many other regions, including those planned for extractive activities, lack the information needed.

Experimental seabed disturbance effects on Chatham Rise deep‐sea meiofaunal communities, Southwest Pacific - Daniel Leduc; Campbell Murray; Ashley A. Rowden; Scott D. Nodder; Rachel Hale; Malcolm R. Clark (New Zealand Journal of Marine and Freshwater Research, 2025)
Growing global demand for deep‐sea resources may lead to increased pressure on benthic ecosystems. Here we examined changes in meiofaunal communities following an in situ physical disturbance experiment. A significant change in meiofaunal community structure in surface (0‐1 cm) and subsurface (1‐5 cm) sediments was observed immediately following the disturbance at both the directly and indirectly disturbed sites and adjacent potentially undisturbed/indirectly disturbed sites, reflecting a decrease in the abundance of several meiofaunal taxa. Abundance, taxon richness and diversity also decreased immediately following disturbance across all sites. Surface community parameters returned to pre‐disturbance values one year post‐disturbance, but only a partial recovery was observed for the subsurface community over the same period. The accumulation of recently resuspended and deposited sediment could have led to lower meiofaunal density and shifts in community structure. Passive dispersal and recolonisation from outside the study area may explain why the surface community recovered more fully than the subsurface community. We show that meiofauna were negatively affected by a relatively minor disturbance compared to proposed commercial seabed mining operations, but the finding that communities had largely recovered one year after disturbance has implications for resilience of fauna to much more pronounced impacts of potential large‐scale mining.

Effects of experimental in situ seabed disturbance on deep‐sea macrofaunal communities of Chatham Rise, Southwest Pacific - Campbell Murray; Ashley A. Rowden; Daniel Leduc; Scott D. Nodder; Rachel Hale; Jane Halliday; Malcolm R. Clark (New Zealand Journal of Marine and Freshwater Research, 2025)
With the possibility of deep‐sea mining of mineral resources occurring, it is necessary to understand potential impacts on benthic communities. Previous simulated mining experiments revealed direct benthic impacts; however, indirect impacts of sedimentation are not well understood. A disturbance experiment was conducted on Chatham Rise, New Zealand, to assess the resilience of benthic communities to sedimentation that could result from future deep‐sea phosphorite mining. Macrofaunal and sediment samples were collected before, immediately after, and one year after a disturbance in areas directly physically disturbed and subjected to induced sedimentation (DI), and undisturbed or subjected to sedimentation only (UI). Macrofaunal abundance significantly decreased in DI areas but not in UI areas. However, abundance‐based community structure changed in both areas; in DI areas this was mostly driven by decreases in dominant fauna, but in UI areas by changes in more sensitive fauna. One year after disturbance, abundance‐based community structure had recovered in both areas and was correlated most strongly with variations in sediment C:N molar ratios. Biomass‐based community structure in DI areas differed one‐year post disturbance from communities sampled at the two earlier periods. These results are useful for informing the management of impacts from offshore industries where sedimentation is an issue.

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

The role of wind and buoyancy forcing on mixed layer depths and productivity on the Chatham Rise from ocean glider and ship‐based observations - Charine Collins; Joe O’Callaghan; Malcolm R. Clark; Scott D. Nodder (New Zealand Journal of Marine and Freshwater Research, 2025)
The Subtropical Front (STF) and associated biological productivity are topographically locked to the Chatham Rise. Year‐to‐year differences of upper ocean dynamics and associated responses of phytoplankton are valuable for understanding variability in fisheries biomass as well as providing new knowledge of environmental condition for potential seabed mining in this keystone ecosystem. In‐situ observations collected over three consecutive years are used to examine the oceanographic variability on Chatham Rise and its potential causal mechanisms are evaluated from satellite observations and a global atmospheric reanalysis. The water column over Chatham Rise consists of a three‐layer structure comprised of a stable intermediate layer sandwiched between a well‐mixed surface and bottom layer. The in‐situ data showed that different water masses can dominate the surface mixed layer at different times. This variability in surface water masses appears to be related to the position of the STF modulated by wind forcing. Spatial and temporal variability was also observed in the mixed layer depth with the temporal variability driven mainly by wind forcing. A strong relationship was observed between phytoplankton biomass and the depth of the mixed layer with implications for the distribution of biological communities and fisheries at the year‐to‐year timescale on the Chatham Rise.

Earthquake-triggered submarine canyon flushing transfers young terrestrial and marine organic carbon into the deep sea - Katherine L Maier; Catherine E Ginnane; Sebastian Naeher; Jocelyn C Turnbull; Scott D Nodder; Jamie Howarth; Sarah J Bury; Robert G Hilton; Jess IT Hillman (Earth and Planetary Science Letters, 2025)

Bioturbation and faunal-mediated ecosystem functioning in a deep-sea benthic community recovering from a severe seabed disturbance - Rachel Hale; Katharine T. Bigham; Ashley A. Rowden; Jane Halliday; Scott D. Nodder; Alan R. Orpin; Grace Frontin-Rollet; Katherine L. Maier; Joshu J. Mountjoy; Matthew H. Pinkerton (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Deep-sea macrofauna community recovery in Kaikōura canyon following an earthquake-triggered turbidity flow - Katharine T. Bigham; Ashley A. Rowden; Daniel Leduc; David A. Bowden; Scott D. Nodder; Alan R. Orpin; Jane Halliday (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Reduction in size of the calcifying phytoplankton Calcidiscus leptoporus to environmental changes between the Holocene and modern Subantarctic Southern Ocean - Andrés S. Rigual-Hernández; Gerald Langer; Francisco Javier Sierro; Helen Bostock; José Manuel Sánchez-Santos; Scott Davidson Nodder; Tom W. Trull; Anne Marie Ballegeer; Andrew D. Moy; Ruth Eriksen; Laura Makowka; Thibauld M. Béjard; et al. (Frontiers in Marine Science, 2023)
The Subantarctic Zone of the Southern Ocean plays a disproportionally large role on the Earth system. Model projections predict rapid environmental change in the coming decades, including ocean acidification, warming, and changes in nutrient supply which pose a serious risk for marine ecosystems. Yet despite the importance of the Subantarctic Zone, annual and inter-annual time series are extremely rare, leading to important uncertainties about the current state of its ecosystems and hindering predictions of future response to climate change. Moreover, as the longest observational time series available are only a few decades long, it remains unknown whether marine pelagic ecosystems have already responded to ongoing environmental change during the industrial era. Here, we take advantage of multiple sampling efforts – monitoring of surface layer water properties together with sediment trap, seafloor sediment and sediment core sampling – to reconstruct the modern and pre-industrial state of the keystone calcifying phytoplankton Calcidiscus leptoporus , central to the global marine carbonate cycle. Morphometric measurements reveal that modern C. leptoporus coccoliths are 15% lighter and 25% smaller than those preserved in the underlying Holocene-aged sediments. The cumulative effect of multiple environmental factors appears responsible for the coccolith size variations since the Last Deglaciation, with warming and ocean acidification most likely playing a predominant role during the industrial era. Notably, extrapolation of our results suggests a future reduction in cell and coccolith size which will have a negative impact on the efficiency of the biological pump in the Southern Ocean through a reduction of carbonate ballasting. Lastly, our results tentatively suggest that C. leptoporus coccolith size could be used as a palaeo-proxy for growth rate. Future culture experiments will be needed to test this hypothesis.

Deep-sea benthic megafauna hotspot shows indication of resilience to impact from massive turbidity flow - Katharine T. Bigham; Ashley A. Rowden; David A. Bowden; Daniel Leduc; Arne Pallentin; Caroline Chin; Joshu J. Mountjoy; Scott D. Nodder; Alan R. Orpin (Frontiers in Marine Science, 2023)
Sediment density flows are large scale disturbances that can have dramatic impacts on seafloor animal communities in the deep sea. Seafloor imagery collected in Kaikōura Canyon (New Zealand), before and after a sediment density flow event that included debris and turbidity flows triggered by a 2016 M w 7.8 Kaikōura Earthquake, shows the recovery trajectory of the animal community in the canyon head in the weeks, months, and years following the disturbance. The canyon community appears resilient to this event, with models estimating full recovery within a minimum of 4.5–5.1 years and as long as 12 years. The implications of the resilience of this deep-sea community are discussed in the context of the local marine protected area, the surrounding fishery, and global seabed mining.

Structure of infaunal communities in New Zealand submarine canyons is linked to origins of sediment organic matter - Daniel Leduc; Scott D. Nodder; Ashley A. Rowden; Max Gibbs; Katrin Berkenbusch; Anna Wood; Fabio De Leo; Craig Smith; Julie Brown; Sarah J. Bury; Arne Pallentin (Limnology and Oceanography, 2020)
Submarine canyons can facilitate the transfer of land‐derived organic matter to the deep sea. Here, we investigated links between variability in organic matter availability from land and marine sources and infauna communities in two contrasting canyon systems off New Zealand and used stable isotope analyses to identify potential food sources of benthic invertebrates. Kaikōura Canyon, a steep, short canyon close to the shore, was characterized by high food availability and varying proportions of marine‐ and land‐derived organic matter, whereas Hokitika Canyon, a narrow and lower‐gradient canyon that extends further from the coast, was characterized by low food availability and mostly land‐derived sediment organic matter throughout. Both macrofaunal and meiofaunal abundance and biomass were greater in Kaikōura Canyon than in Hokitika Canyon. Correlation analyses suggested that land‐derived organic matter may contribute to increased meiofaunal abundance in Kaikōura Canyon. Carbon and nitrogen isotopic analyses, however, did not provide unequivocal support for the uptake of land‐derived material by large benthic invertebrates in Kaikōura Canyon. Infaunal abundance and biomass were low throughout Hokitika Canyon despite similar concentrations of land‐derived organic matter in sediments of both canyons, which suggests that variations in marine‐derived organic matter inputs is the main driver of community differences among canyons. Refractory vascular plant material by itself may not provide an adequate food supply to infaunal organisms, but may represent a complementary food resource when more labile marine phytodetritus is also readily available.

Novel Application of a Compound-Specific Stable Isotope (CSSI) Tracking Technique Demonstrates Connectivity Between Terrestrial and Deep-Sea Ecosystems via Submarine Canyons - Max Gibbs; Daniel Leduc; Scott D. Nodder; Andrew Kingston; Andrew Swales; Ashley A. Rowden; Joshu Mountjoy; Greg Olsen; Ron Ovenden; Julie Brown; Sarah Bury; Brittany Graham (Frontiers in Marine Science, 2020)

Developing an Integrated Ocean Observing System for New Zealand - Joanne O’Callaghan; Craig Stevens; Moninya Roughan; Chris Cornelisen; Philip Sutton; Sally Garrett; Giacomo Giorli; Robert O. Smith; Kim I. Currie; Sutara H. Suanda; Michael Williams; Melissa Bowen; et al. (Frontiers in Marine Science, 2019)

Effect of core surface area and sediment depth on estimates of deep-sea nematode genus richness and community structure - Daniel Leduc; Scott D. Nodder; Katrin Berkenbusch; Ashley A. Rowden (Marine Biodiversity, 2015)

Differential remineralization of major and trace elements in sinking diatoms - Benjamin S. Twining; Scott D. Nodder; Andrew L. King; David A. Hutchins; Gary R. LeCleir; Jennifer M. DeBruyn; Elizabeth W. Maas; Stefan Vogt; Steven W. Wilhelm; Philip W. Boyd (Limnology and Oceanography, 2014)
Macronutrients in sinking phytoplankton are typically remineralized at different rates, but less is known about the fate of micronutrient metals associated with sinking cells. Scavenging, the presence of co‐occurring abiotic particles, and inadvertent contamination limit the utility of bulk analytical approaches to study remineralization of trace metals in sinking phytoplankton. We used synchrotron x‐ray fluorescence mapping to measure macronutrients (P, S, and Si) and trace metals (Fe, Ni, and Zn) in individual cells of the diatom Asterionellopsis glacialis during a spring bloom in subtropical waters off New Zealand. P, S, Zn, and Ni were released significantly faster than Fe and Si from sinking cells in the upper 200 m. Bulk particulate element fluxes to sediment traps indicated similar trends, but biogenic silica flux was attenuated much faster than Si was lost from intact sinking cells collected in the traps. The metals were spatially co‐located with P and S in upper ocean cells, but this association with P and S (based on a spatial resolution of 450 nm) was largely absent in sinking cells. In contrast, Fe retained a weak spatial association with Si, suggesting that remineralized Fe may be re‐scavenged onto cell surfaces. As a result, dissolved Fe : macronutrient stoichiometries in the water column likely underestimate stoichiometries in sinking cells. We propose linkages between the selective loss of diatom cellular components (e.g., ribosomes or phospholipid membranes, Zn‐finger proteins, and urease) and the observed recycling of specific elements (P, Zn, and Ni, respectively), which set the stoichiometry of macro‐ and micronutrient supply to surface waters.

Focusing of phytodetritus deposition beneath a deep‐ocean front, Chatham Rise, New Zealand - Scott D. Nodder; Gerard C. A. Duineveld; Conrad A. Pilditch; Philip J. Sutton; P. Keith Probert; Marc S. S. Lavaleye; Rob Witbaard; F. Hoe Chang; Julie A. Hall; Ken M. Richardson (Limnology and Oceanography, 2007)
In October 2001, we observed a deep‐ocean phytodetritus deposition event on Chatham Rise beneath the Subtropical Front (STF). The origin of this phytodetritus was probably an extensive phytoplankton bloom that occurred in the STF in the preceding weeks. We assessed the spatial distribution of the deposition event using video images from benthic lander and epibenthic trawl deployments and sediment pigment analyses at six sites on a north—south transect across Chatham Rise. High surficial sediment chlorophyll a concentrations were restricted spatially to the southern flank of Chatham Rise (350–1,200‐m depth) with the highest values centered at ~750‐m water depth (750 S). This southern 750 S site was also the only site where macroscopic phytodetritus was observed, coincident with elevated benthic biomass and sediment community respiration rates. At 750 S, phytodetritus resuspension was observed on video and corroborated by current meter, sediment trap, and optical backscatter measurements, suggesting a threshold erosion current speed for phytodetritus of ~10 cm s −1 , equivalent to a shear velocity of 0.5 cm s −1 and similar to other deep‐ocean studies elsewhere. The restriction of macroscopic phytodetritus deposition to 750 S was related to a zone of current convergence within the STF and lower near‐bed current speeds observed across ~1‐day that promoted deposition. Observations of high benthic biomass and respiration on the southern flank of Chatham Rise suggest that this focusing process is important in fueling the energy demands of benthic communities, in association with the general west‐east advection of organic matter within the STF itself. Such physical focusing of labile organic matter deposition may be an important process in other highly productive frontal systems.

Mass sedimentation of picoplankton embedded in organic aggregates - Anya M. Waite; Karl A. Safi; Julie A. Hall; Scott D. Nodder (Limnology and Oceanography, 2000)
During a survey cruise crossing the Subtropical Front over the Chatham Rise east of New Zealand, we made the first observation in High Nutrient Low Chlorophyll waters of massive sedimentation of picoplankton embedded in large (>0.5 mm diam.) organic aggregates (OAs) sensu Riley (1963). We estimate 9.3 mg C m ‐2 yr ‐1 of prokaryotic picoplankton biomass alone may be transported below the euphotic zone via this mechanism. Using confocal microscopy, we made direct observations of picoplankton within undisrupted individual OAs, collected in sediment traps fitted with acrylimide gels, which largely conserved particle structure. Prokaryotic picoplankton autofluoresc‐ence was well‐preserved and concentrations were extremely high within large rapidly sedimenting aggregates, ranging from 1.06 × 10 8 ml ‐1 in the 120 m sediment traps in subantarctic waters to 7.5 × 10 6 ml ‐1 at 550 m in subtropical waters, yielding Enrichment Factors of 10 3 — 10 5 relative to picoplankton concentrations in the water column. Aggregate picoplankton concentrations showed a well‐constrained exponential decline with depth, which we speculate may represent an estimate of protozoan grazing rate within the aggregates. Picoplankton were found within heterotrophic flagellates, within copepod fecal pellets, and within organic matrices, all of which were incorporated in OAs. The key event of picoplankton incorporation into initial particles occurs in the upper water column, very likely through grazing with low assimilation efficiency. Once OAs are formed, their changing porosity and reduction in picoplankton cell numbers via heterotrophy is likely to be a key factor mediating picoplankton carbon fluxes in moderately productive ecosystems, and in determining the overall particle structure of sedimenting OAs.